2017
DOI: 10.1111/hcre.12111
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Media Multitasking and Attention Problems in Adolescents: Results of Two Longitudinal Studies

Abstract: The increased prevalence of media multitasking among adolescents has raised concerns that media multitasking may cause attention problems. Despite cross-sectional evidence of the relationship between media multitasking and attention problems, no study has yet investigated this relationship longitudinally. It is therefore unclear how these two variables are related. Two 3-wave longitudinal studies with 3-and 6-month time lags were conducted. In total, 2,390 adolescents aged 11-16 provided data on media multitas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…Recently, Hamaker, Kuiper, and Grasman (2015) suggested a modified random intercept CLPM that accounts for both within-and between-person effects, with the cross-lagged effects on the within-person level. We agree with Baumgartner et al (2017) that the RI-CLPM currently seems the best statistical model to empirically test the RSM, and their results seem to deliver on that promise in terms of model fit and interpretability. However, only few studies in communication research have used this model, so we have to wait whether this solves the statistical issues in identifying reinforcing spirals in communication research.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, Hamaker, Kuiper, and Grasman (2015) suggested a modified random intercept CLPM that accounts for both within-and between-person effects, with the cross-lagged effects on the within-person level. We agree with Baumgartner et al (2017) that the RI-CLPM currently seems the best statistical model to empirically test the RSM, and their results seem to deliver on that promise in terms of model fit and interpretability. However, only few studies in communication research have used this model, so we have to wait whether this solves the statistical issues in identifying reinforcing spirals in communication research.…”
Section: Discussionsupporting
confidence: 82%
“…On this reciprocity, several longitudinal studies have attempted to examine whether media multitasking behavior and everyday-related problems are reinforcing each other over a longer time period. The results of these studies showed that media multitasking did not appear to have a reciprocal relationship with the occurrence attentional problems (Baumgartner, van der Schuur, Lemmens, & Te Poel, 2017) 3 and 6 months later. Nevertheless, these studies showed that the associations between media multitasking and attentional problems were stable over time.…”
Section: Notes On Causalitymentioning
confidence: 80%
“…Lastly, one article was excluded since the relevant effect sizes could not be extracted from the published article (Shih, 2013) 2 . In all, a total of 13 articles containing 15 independent studies 3 were included for synthesis (Baumgartner, van der Schuur et al, 2017Cain et al, 2016;Cardoso-Leite et al, 2015;Duff, Yoon, Wang, & Anghelcev, 2014;Hadlington & Murphy, 2018;Magen, 2017;Minear et al, 2013;Ralph et al, 2013;Sanbonmatsu et al, 2013;Schutten et al, 2017;Uncapher et al, 2016;Yang & Zhu, 2016). Table 1 shows the measures of self-reported functioning included in each study and the number of participants assessed.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this development, researchers have begun to examine how the frequency of media multitasking relates to various indices of personality, mental health, and cognition (for reviews, see Carrier, Rosen, Cheever, & Lim, 2015;Courage, Bakhtiar, Fitzpatrick, Kenny, & Brandeau, 2015;Uncapher et al, 2017;Van Der Schuur, Baumgartner, Sumter, & Valkenburg, 2015). On the one hand, several studies showed evidence for a weak association of media multitasking with selfreport measures of impulsivity and sensation-seeking (e.g., Minear, Brasher, McCurdy, Lewis, & Younggren, 2013;Sanbonmatsu, Strayer, Medeiros-Ward, & Watson, 2013) and attention-deficit hyperactivity disorder (ADHD)-related symptoms (Baumgartner, van der Schuur, Lemmens, & te Poel, 2017a;Magen, 2017;Uncapher, Thieu, & Wagner, 2016). On the other hand, however, studies exploring the correlates of media multitasking in laboratory measures of selective attention, working memory, and executive control have thus far produced less compelling results.…”
Section: Introductionmentioning
confidence: 99%